UPAYA PENCEGAHAN COVID-19 DENGAN PRINSIP 3M(Mencuci Tangan, Memakai Masker Dan Menjaga Jarak) DI PULAU PANJANG KOTA BATAM - Desi Ernita Amru; Mona Rahayu Putri, Anisya Selvia, Siti Husaidah, Hamdiah Ahmar (JOURNAL OF COMMUNITY DEDICATION, 2021)
Indonesia is still struggling with the Corona virus until now, the same as other countries in the world. The number of cases of the Corona virus continues to grow with some reporting recoveries, but not a few who have died. Steps that are now believed all over the world are disciplined use of masks when doing activities, diligently washing hands with soap and running water and maintaining social distance. The method used in this community service activity is to provide counseling and conduct demonstrations on the implementation of 3M (Washing Hands, Wearing Masks, Keeping Your Distance). After the activity was carried out, the counseling participants were quite enthusiastic and also the residents of Panjang Island were very supportive of the COVID-19 transmission prevention program.